North African mosaic : a cultural reappraisal of ethnic and religious minorities - Boudraa, Nabil; Krause, Joseph (Cambridge Scholars Pub., 2007)
This book's ambition is to offer the most recent scholarship on North African cultures at a time when the very notion of culture is being re-evaluated in the shifting tides that both associate and divorce the forces of nationalism, globalism and neo-liberalism. Another ambition is to be a readable document about the past and the potential of North African civilizations. Those which have been crystallized into a polysemic voice from centuries of occupations, exchanges and what is now commonly ...